Comparison of Foliar Verses Soil Application of Micronutrients on the Production of Wheat (Triticum aestivum. L) Crop. - Arshad Ali Kaleri; Mukesh Kumar Soothar; Barkat Ali; Saeed Ahmed; Aurang Zaib; Abdul Jabbar Chandio; Feroz Gul Nizamani; Ayaz Ali Pahnwar (Journal of Basic & Applied Sciences, 2018)
The present work was laid out to compare the effect of foliar verses soil application of micronutrients on the production of wheat crop at experimental side of southern wheat station Agriculture Research Institute Tandojam, during Rabi season 2016. There were ten fertilizer treatments viz T1= K2%, T2= 1% Zn, T3= B 0.2%, T4= Cu 2%, T5= Mg 1% as foliar application while T6= 6Kg Zn ha-1, T7= 3.5Kg B ha-1 (Borax) T8= 5Kg Cu ha-1 (CuSo4), untreated T9 tried with an standard dose of 230-115 Kg and NP ha-1 was (T10). The experiment was laid out in three replicated Randomized Complete Block Design. It was observed that plant height, tillers plant-1, spike length, grains spike-1, 1000 grain weight and grain yield ha-1 differed significant between all the treatments. Soil application of 6 Kg ha-1 Zn gave maximum grain yield of 5113.33 Kg ha-1, this increscent in yield was associated with significant increase in tillers plant-1 of 20.81.Spike length of 13.84 cm, grain spike-1 of 71.95 and 1000 seed weight was 68.66 respectively. It is concluded that soil application of micronutrients were relatively more effective than foliar application in local soil condition. Among the micronutrients Zn applied at 6 Kg ha-1, followed by 3 Kg Mg ha-1 and 3.5 Kg B ha-1 gave higher grain yield due to increased values in all yield related parameters.